2010
DOI: 10.1002/pola.24318
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of poly(N‐9‐ethylcarbazole‐exo‐norbornene‐5,6‐dicarboximide) for hole‐transporting layer in hybrid organic light‐emitting devices

Abstract: We synthesized new polynorbornene dicarboximide (PCaNI) functionalized with hole‐transporting carbazole moieties and its copolymer (PCaNA) by ring‐opening metathesis polymerization (ROMP), where the PCaNA was further reacted with 3‐amino‐triethoxysilane to prepare PCaNI/silica hybrid. We also investigated the feasibility of PCaNI and PCaNI/silica hybrid (PCaSi) as a hole‐transporting material for hybrid organic light emitting devices (HOLEDs). To improve the performance of the PCaNI‐based HOLEDs, N,N′‐diphenyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…3 A small selection of these interesting applications include cell adhesion materials, membranes, insulating materials and various optics applications. [4][5][6][7][8][9] This breadth of applications can be attributed to the fact that, as a polymer class, poly(NDI)s have been demonstrated to exhibit favorable thermal and mechanical properties, which greatly extend their range of practical applications. [10][11][12][13][14] Furthermore, ring-opening metathesis polymerization allows the preparation of well-defined random, block and alternating copolymers that extend the utility of poly(NDI)s as a system to prepare reactive and functional polymers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 A small selection of these interesting applications include cell adhesion materials, membranes, insulating materials and various optics applications. [4][5][6][7][8][9] This breadth of applications can be attributed to the fact that, as a polymer class, poly(NDI)s have been demonstrated to exhibit favorable thermal and mechanical properties, which greatly extend their range of practical applications. [10][11][12][13][14] Furthermore, ring-opening metathesis polymerization allows the preparation of well-defined random, block and alternating copolymers that extend the utility of poly(NDI)s as a system to prepare reactive and functional polymers.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14] Furthermore, ring-opening metathesis polymerization allows the preparation of well-defined random, block and alternating copolymers that extend the utility of poly(NDI)s as a system to prepare reactive and functional polymers. 15,16 Therefore, a systematic study of the influence of the Grubbs initiator on the precise controllability of the molecular weight and stereochemistry of a standard NDI monomer is of practical utility. Monomer preparation for poly(NDI)s is simple and easy.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, ROMP appears to be an interesting method also for fabricating side chain-type carbazole-containing polymers. Some examples of ROMP of norbornene-based monomers containing carbazole groups promoted by Grubbs catalysts are described in the literature [38][39][40][41]. Recently, Zeng et al also reported the synthesis of highly efficient blue thermally activated delayed fluorescence polymers and copolymers based on side chain-type carbazole-containing polymers obtained by using Grubbs second-generation catalyst [42].…”
Section: Introductionmentioning
confidence: 99%
“…Ring‐opening metathesis polymerization (ROMP) offers an effective way to polymerize norbornene monomers with different side chain substitutes 26. Grubbs' ruthenium (Ru) carbene complexes efficiently catalyze ROMP under ambient conditions, with a high tolerance for polar functional groups 27–32. Thus, the use of a Ru‐based catalyst in ROMP is a promising route to prepare polynorbornenes with colorless, transparent, and easily solution‐processable properties.…”
Section: Introductionmentioning
confidence: 99%